"Dying for a Baby" and Other "Confusions of Tongues": A Discussion of "Childless". Issue 1 (2nd January 2019) - Gentile, Katie
Abstract : This paper discusses the beautiful case presented by Rebeccca Harrington in "Childless." This discussion focuses on Harrington's narrated ambivalences around reproduction and the traumatic repetitions experienced by her patient Shira. As her case unfolds, Harrington recognizes the ways her silences around Shira's engagement with assisted reproductive technologies reenacted a form of a parental blindness to abuse. Building on Harrington's ideas, this discussion integrates queer and psychoanalytic theory to ponder some ways the fetus has become a fetish for U.S. culture and how this shift appears to be a form of temporally based affect regulation that collapses spaces of ambivalence around maternity for women. Within these cultural dynamics, this discussion emphasizes Harrington's call for psychoanalysis as a field to analyze its own pronatalist agenda.